2021
DOI: 10.1017/pds.2021.516
|View full text |Cite
|
Sign up to set email alerts
|

Representation and Application of Digital Standards Using Knowledge Graphs

Abstract: Standards are an important source of knowledge in product development. Due to the increasing digitization of the product development process, standard development organizations aim to develop machine-actionable standards that automatically enforce operations in output devices. However, the current representation format in PDF or XML does not meet the requirements of machine-actionable standards. This paper examines existing approaches towards the representation of XML data in knowledge graphs and their transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Hereby, a KG is a semantic network that interconnects data by representing entities and their relations whereas the knowledge structure is referred to as ontology (Huang et al, 2023). The KG creation from engineering standards was demonstrated using the example of mathematical equations that were automatically extracted from XML standards, transferred to graph patterns, and provided via flexible interfaces (Luttmer et al, 2021). It should be noted, however, that only the equations and metadata, such as the standard number, were extracted, and no further contextual, descriptive elements for the correct interpretation of the equation were included.…”
Section: Trends Towards Machine-actionable and Machine-interpretable ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Hereby, a KG is a semantic network that interconnects data by representing entities and their relations whereas the knowledge structure is referred to as ontology (Huang et al, 2023). The KG creation from engineering standards was demonstrated using the example of mathematical equations that were automatically extracted from XML standards, transferred to graph patterns, and provided via flexible interfaces (Luttmer et al, 2021). It should be noted, however, that only the equations and metadata, such as the standard number, were extracted, and no further contextual, descriptive elements for the correct interpretation of the equation were included.…”
Section: Trends Towards Machine-actionable and Machine-interpretable ...mentioning
confidence: 99%
“…Existent content provision formats like PDF and even XML in NISO STS are not sufficiently considering semantic relations (Loibl et al, 2020). Building upon the research work of Luttmer et al (2021), knowledge graphs have demonstrated their efficacy in serving as semantically enriched knowledge representation of standards. However, the previous approach focused solely on mathematical equations whereas contextual elements such as symbol definitions and relations between equations were not included, limiting the correct interpretation and application of equations.…”
Section: Research Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…To automate this process, there is already research in extracting knowledge from standards (Luttmer et al 2021) supported by recent developments of the American National Information Standards Organization (NISO) for establishing a XML tag set defined as NISO-STS which is based on the ISO Standard Tag Set (Wheeler et al 2016). Additional opportunities are provided by "technical language processing" where the emerging technology of natural language processing is applied to technical documents (Brundage et al 2021) or their classification (Jiang et al 2022).…”
Section: Documentationmentioning
confidence: 99%
“…In these approaches, design rules are often manually written in code like SWRL or pseudo-code like SADL. However, significant progress have been made in the automated capture of design knowledge into computable semantic relations [17]- [20]. These technologies lead to more flexible CAD quality software that integrate varying design rules.…”
Section: Cognitive Assistantmentioning
confidence: 99%